Effect of the dialysis fluid buffer on peritoneal membrane function in children - Schmitt, Claus P.; Nau, Barbara Silvia; Gemulla, Gita; Sander, Anja; Schaefer, Franz (Clinical journal of the American Society of Nephrology, 2013)
Background and objectives: Double-chamber peritoneal dialysis fluids exert less toxicity by their neutral pH and reduced glucose degradation product content. The role of the buffer compound (lactate and bicarbonate) has not been defined in humans. Design, setting, participants, & measurements: A multicenter randomized controlled trial in 37 children on automated peritoneal dialysis was performed. After a 2-month run-in period with conventional peritoneal dialysis fluids, patients were randomized to neutral-pH, low-glucose degradation product peritoneal dialysis fluids with 35 mM lactate or 34 mM bicarbonate content. Clinical and biochemical monitoring was performed monthly, and peritoneal equilibration tests and 24-hour clearance studies were performed at 0, 3, 6, and 10 months. Results: No statistically significant difference in capillary blood pH, serum bicarbonate, or oral buffer supplementation emerged during the study. At baseline, peritoneal solute equilibration and clearance rates were similar. During the study, 4-hour dialysis to plasma ratio of creatinine tended to increase, and 24-hour dialytic creatinine and phosphate clearance increased with lactate peritoneal dialysis fluid but not with bicarbonate peritoneal dialysis fluid. Daily net ultrafiltration, which was similar at baseline (lactate fluid=5.4±2.6 ml/g glucose exposure, bicarbonate fluid=4.9±1.9 ml/g glucose exposure), decreased to 4.6±1.0 ml/g glucose exposure in the lactate peritoneal dialysis fluid group, whereas it increased to 5.1±1.7 ml/g glucose exposure in the bicarbonate content peritoneal dialysis fluid group (P=0.006 for interaction). Conclusions: When using biocompatible peritoneal dialysis fluids, equally good acidosis control is achieved with lactate and bicarbonate buffers. Improved long-term preservation of peritoneal membrane function may, however, be achieved with bicarbonate-based peritoneal dialysis fluids.